Modern a cappella-pop and showchoir methods for the classically trained music educator - Cassidy, Timothy John (Kansas State University, 2013)
University choral music education programs commonly focus on training music educators in the Western Classical tradition, however, the evolving landscape of popular music requires an additional set of skills and experiences that are not a part of the standard curriculum. A cappella groups with vocal percussion and show choirs are increasing in demand due to the popularity of modern vocal music entertainment with television shows such as “Glee” and “The Sing-off” and performing groups such as “Pentatonix” and “Straight No Chaser.” With limited available literature and training, current and future musical educators face the problem of having to acquire these skills on their own. While ensembles dedicated to singing popular music are nothing new, the technical aspects of developing an ensemble that meets the high performance expectations of modern audiences can be intimidating. This report intends to cover the requisite techniques, skills, and resources that modern a cappella pop choirs and show choirs utilize to be successful. The report covers these topics: 1) a brief survey of the historical origins of choral vocal pop and show choir ensembles 2) defining the purpose, intent, and nature of such ensembles 3) show choirs, pop a cappella choirs, and hybrids 4) roles, responsibilities, and personnel assignment 5) music selection, arrangement, and programming 6) the decision to perform live, with a pre-recorded track, or a combination 7) use of audio and recording equipment in performance 8) rehearsal techniques 9) artistic and stylistic decisions
Keywords: Show choir; Pop choir; Methods; Arranging; Techniques; Technology; Music (0413)